A Web-Based System for Photovoltaic Energy Generation: Use of Mathematical Models for Irradiance in Brazil - Nunes, Isabelle F. S.; Barros, Tárcio A. S.; Fantinato, Denis G. (Anais da Escola Regional de Informática de Goiás (ERI-GO), 2024)
In the context of renewable energy generation, software tools are essential for addressing the sector’s main challenges. For instance, Photovoltaic (PV) energy demands a study of the PV plant allocation before its deployment to improve efficiency. However, the visualization tools that perform this task face some usability issues, such as the complementary artifacts to analyze and data-driven modeling. In that sense, this work proposes an artifact with an intuitive and user-friendly platform built as a web-based application with open-source technologies, considering the PV mathematical models. The web-based system gathers a set of mathematical models available and was tested for Brazilian irradiance simulation, allowing inclined plane analysis and other variants.